Effects of Cultural Stress on Identity Development and Depression among Hispanic College Students. Issue 1 (2nd January 2022) - Meca, Alan; Webb, Taylor; Cowan, Isis; Moulder, Alicia; Schwartz, Seth J.; Szabó, Ágnes; Ward, Colleen
ABSTRACT: Hispanic emerging adults are routinely faced with a variety of cultural stressors that adversely impact mental health and compromise identity development. Given that identity emerges through day-to-day interactions, there is a need to explore the impact of cultural stress on identity development and depressive symptoms at the micro-level (across days). To address these gaps, the current study utilized a 12-day diary study conducted among 792 Hispanic college students (75.9% female, M age = 20.14 years, SD = 1.85, Range = 18–24 years) to determine the impact of cultural stress on daily identity coherence, identity confusion, depressive symptoms, and the association between identity coherence and confusion and depressive symptoms in this population. Results indicated that Day 1 cultural stress positively predicted average daily depressive symptoms and identity confusion and negatively predicted identity coherence. Finally, cultural stress predicted a stronger daily association between identity confusion and depressive symptoms. As a whole, our findings emphasize the detrimental impact that cultural stressors have on both identity development and depressive symptoms at the daily level. These results are discussed in relation to the specific types of cultural stressors that Hispanic emerging adults face, and the need for appropriate intervention and prevention efforts for this population is emphasized.